Imagery improves reaction time in elite sprinters - Iftikhar, M.; Mallett, C.; Javed, M. (Proceedings of the 6th International Conference on Sport Sciences Research and Technology Support - Volume 1: icSPORTS, 2018)
Motor imagery has been found to be helpful for developing skills in sport. Motor imagery (MI) helps an athlete to visualize simple or complex motor activities in the absence of physical practice. Few studies have inspected the effects of motor imagery on trained individuals. The purpose of this study was to investigate the effects of motor imagery on reaction time. Differences in reaction time can make a difference in terms of the overall performance (time, ranking). Twenty-four male and female National elite athletes (12 male; age: 22.92+1.73 years and 12 female; age: 22.67+1.67 years), who participated in this study, were classified into two (2) groups. Participants were classified according to data from a pretest in which they recorded their reaction time (ms) on starting blocks and a 30 meters race time (s). The control group (N=12) carried out the practice physically and the imagery (intervention) group (N=12) firstly carried out the practice mentally and then physically with th e control group. Motor Imagery was conducted on the experimental group for fifteen (15) minutes every day for two (2) weeks. At the end of two (2) weeks, a post-test was conducted to examine any intervention effects. The data were analyzed by a paired t-test. The findings revealed that imagery group athletes improved more than the control group (p < 0.05). A couple of the athletes from the physical practice group (no intervention) showed better results than the imagery group, but the researcher observed the potential reason behind this enhancement might have been due to the competitive atmosphere created due the experiment for which they put their best to beat the other group in the post test.